Numerical simulation of missile warhead operation. (September 2018) - Martynenko, G.; Chernobryvko, M.; Avramov, K.; Martynenko, V.; Tonkonozhenko, A.; Kozharin, V.; Klymenko, D.
Highlights: The approach for simulations of the warhead fracture is suggested in software ANSYS. The analysis of the static stress-strain state of the warhead, which is arisen owing to its assembling. Calculations of the dynamic stress state of the structure. Analysis of dynamic fracture of the most loaded units. The parameters of the warhead are chosen in order to a fracture takes place in the structure specified area. Abstract: Numerical simulation of a missile warhead dynamic fracture is considered. The design of the warhead basic units is treated. The approach for simulations of the warhead fracture in software ANSYS is proposed. This approach is split on three stages. (I). The analysis of the static stress-strain state of the warhead, which is arisen owing to its assembling. (II). Calculations of the dynamic stress state of the structure. (III). Analysis of dynamic fracture of the most loaded units. The parameters of the warhead are chosen in order to a fracture takes place in the structure specified area.